2000
DOI: 10.1093/jjco/hyd071
|View full text |Cite
|
Sign up to set email alerts
|

Survival Results of Neoadjuvant Chemotherapy for Advanced Squamous Cell Carcinoma of the Head and Neck

Abstract: NAC does not appear to play a role in the treatment of cancer of the oral cavity and pharynx with our PEM regimen. However, the degree of toxicity was limited in our trial and therefore attempts to increase the dosage and/or revise the administration schedule for cancer of the pharynx and T1 to T3 tumor disease appear warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…Previous studies of preoperative chemotherapy with PF combination regime showed encouraging results in patients with advanced head and neck carcinoma: even though the overall survival was not improved [7,[10][11][12]] , IC achieved high major response (clinical complete or partial response) rate (approximately 48% , range 15%-82%) [7,10,11], with no significant increase in postoperative morbidity and mortality. While other reports [4,[12][13][14] revealed the results with regard to the effect favored IC and the improvement in OS ranged from 4% to 21%.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies of preoperative chemotherapy with PF combination regime showed encouraging results in patients with advanced head and neck carcinoma: even though the overall survival was not improved [7,[10][11][12]] , IC achieved high major response (clinical complete or partial response) rate (approximately 48% , range 15%-82%) [7,10,11], with no significant increase in postoperative morbidity and mortality. While other reports [4,[12][13][14] revealed the results with regard to the effect favored IC and the improvement in OS ranged from 4% to 21%.…”
Section: Discussionmentioning
confidence: 66%
“…Evaluation of these 22 studies found that 8 studies included patients not only with stage III or IV disease but also patients with stage II disease; 4 studies did not clearly describe the tumor status and there was lack of information about the treatment of patients; one study administered chemotherapeutic combinations other than a platinum-based regimen, and two studies were not published in English. Therefore, 7 studies were considered eligible for inclusion in the systematic review and meta-analysis 1215172021. Among the 7 studies, data from 2 studies1317 had to be combined because the latter reported continuous results of the previously published article due to long-term follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, controlled trials with disparate results have created further controversy about the difference between the addition of neoadjuvant chemotherapy with a platinum-based regimen and conventional therapy alone for patients with advanced locoregional HNSCC. While Kohno12 suggested improvement in locoregional control, other investigators101316 found opposite results. While several articles12151719 reported benefits in distant metastasis, Richard14 found it be insignificant, and while certain trials12131920 indicated augmentation in overall survival, others1416182122 supported the conventional locoregional treatment.…”
mentioning
confidence: 98%
“…17 We have also shown that downregulation of Bcl-2 and Bcl-X L enhances the chemotherapeutic efficacy of conventional chemotherapeutic drugs like Cisplatin and Etoposide in HNSCC. Our findings that downregulation of expression of Bcl-2 and Bcl-X L might render HNSCC cells more sensitive to conventional chemotherapeutic agents is supported by the fact that (a) the Bcl-2 family of proteins is the major regulator of mitochondrial permeability and mitochondrial pathway apoptosis, and (b) the mitochondrial pathway, rather than the membrane death receptor pathways, is primarily responsible for chemotherapy induced apoptotic cancer cell death.…”
mentioning
confidence: 81%
“…16 Cisplatin and Etoposide are commonly used for the treatment of advanced as well as recurrent and metastatic head and neck cancers. 17 Bcl-2, Bcl-X L and Survivin overexpression has been found to be associated with chemoresistance to these agents in head and neck cancers. [18][19][20] Since these anti-apoptotic proteins are overexpressed and are responsible for chemoresistance in HNSCC, we wanted to see the effect of antisense-mediated downregulation of these anti-apoptotic genes on apoptosis in HNSCCs and their effect on chemosensitization.…”
Section: Introductionmentioning
confidence: 99%